BIOLOGY. - Richard, Y. K., author 617023; Tan, David, author 225233 (Bangi, Selangor : Penerbitan Pelangi Sdn. Bhd., 2018)
PRE-U sTPM Text Biology Term 1 is specially designed for students who are sitting fo the STPM examination. The compreh nsive notes and practices are based on the latest syllabus and exam format set by Majlis Peperiksaan Malaysia . This book will provide you with the necessary skills and srategies to excel in the subject.